2017
DOI: 10.1149/08002.0053ecst
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Structures Stiction Suppression by Molecular Structure Optimized Surface Energy Reduction Agent

Abstract: Scaling of semiconductor devices has caused nano-structure stiction issues during the drying step of wafer cleaning. We have already proposed a surface modification process to reduce the surface energy, and we have demonstrated this process is more effective for preventing nano-structure stiction than conventional IPA (isopropyl alcohol) drying. In this paper, the proper molecular structure is investigated for surface modification agents. It is important for the suppression of stiction to reduce a surface free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 4 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…In the field of microfabrication, the hydroxyl groups are considered highly reactive and are often seen from the silicon oxide surfaces after SC1 or ozonated water treatment. Therefore, replacing the hydroxyl groups with inactive molecules like silylation agents is a good solution to minimize the stiction [ 243 ]. In ref.243, two kinds of straight-chain alkyl group were compared by means of drying HAR structure evaluation.…”
Section: Wet Cleaningmentioning
confidence: 99%
See 4 more Smart Citations
“…In the field of microfabrication, the hydroxyl groups are considered highly reactive and are often seen from the silicon oxide surfaces after SC1 or ozonated water treatment. Therefore, replacing the hydroxyl groups with inactive molecules like silylation agents is a good solution to minimize the stiction [ 243 ]. In ref.243, two kinds of straight-chain alkyl group were compared by means of drying HAR structure evaluation.…”
Section: Wet Cleaningmentioning
confidence: 99%
“…Attenuated total reflection–infrared spectroscopy (ATR-FTIR) measurements results showed that C1 treatment sufficiently eliminates the hydroxyl groups, as shown in Figure 39 . On the other hand, it is expected that the C8 reaction was suppressed by its steric hindrance, therefore the existing hydroxyl groups could not be sufficiently substituted with alkyl groups [ 243 ]. The drying observation of the HAR structures with aspect ratio of 13.3 using the C1 and C8 confirmed that it is not important to obtain high water repellency, but it is very important to obtain lower surface free energy, as shown in Figure 40 [ 243 ].…”
Section: Wet Cleaningmentioning
confidence: 99%
See 3 more Smart Citations